DEVELOPING AN AUTOMATION SYSTEM FOR GENERATING THE CAD MODEL OF THRUST BALL BEARING - D.Rajendra, Dr.J.Venkatesu Naik, Dr.T. Krishnaiah ,Dr.P.Sneha latha (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Machine parts must be planned according to the requirements. By and large the plan of segments is associated with various computations for getting the necessary subtleties. An intelligent PC program helps in computing the necessary subtleties mulling over of the relative multitude of accessible contributions from the creator. Parametric displaying is the vital innovation for mass customization in plan for fabricate. Knowledge based system (KBS) empowers client to create the necessary model according to the given limitations. In this undertaking work KBS is introduced for the parametric displaying of mechanical parts (latha, bearing) and it has been demonstrated that the KBS turns out appropriately for the diverse stacking conditions. This KBS can uphold displaying of gatherings as the majority of the business CAD frameworks can't deal with the parametric demonstrating of congregations. This framework comprises of a plan information base and a business CAD framework with an API program. The API program interfaces the master framework with the Cad framework through a GUI.